Distributed low-carbon energy management method for port microgrid based on we-energies under polymorphic network - Teng, Fei; Wang, Jianyuan; Luo, Hanguang; Zhang, Qing; Shen, Congqi (Frontiers in Energy Research, 2022)
In order to reduce port pollution and carbon emissions, and improve the utilization rate of clean energy, a port microgrid based on we-energies (WEs) and its polymorphic distributed low-carbon energy management method is proposed. Firstly, the paper considers a variety of heterogeneous WEs such as ship we-energies (SWEs) to establish a polymorphic energy management system for port microgrid and to achieve reliable information exchange between WEs under different communication networks. Secondly, considering the bidirectional energy transmission characteristic of the port WEs, the operating cost function of heterogeneous WEs is established. And then, with the objective of economic and low-carbon operation of port microgrid, the energy management model of port microgrid is constructed and the optimal solution is obtained based on distributed optimization theory. Finally, simulation cases are performed to verify the effectiveness of the proposed method.